Legal Consequences Arising from Non-Compliance in The Process of Mergers and Acquisitions of Technology Companies in Indonesia - Rahayanti Nurmal, Ireina (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
The trend of mergers and acquisitions within technology companies is to strengthen their market positions, but the merger and acquisition process is not an easy one because it involves some complex, diverse legal procedures, and requires strict compliance. The Indonesian government has enacted many legal regulations related to mergers and acquisitions, yet many technology companies do not comply with existing laws. Law No. 5 of 1999 formed the basis for regulating the terms of mergers, consolidations, and acquisitions in articles 28 and 29, Act No. 40 of 2007 on limited companies, and Government Regulation No. 57 of 2010 on Mergers or Mergers of Enterprises and Acquisitions of Shares. This research is shown to better understand the legal consequences that will arise as a result of technology companies in Indonesia failing to comply with the law in the process of mergers and acquisitions. This research uses normative research methods with statute approaches and analytical conceptual approaches. It was found that the development of merger and acquisition law rules in Indonesia has undergone development, changes, and improvements, especially in the notification and merger process. There are several procedures to be followed and anticipated by the company, when one of them is violated, then mergers and acquisitions cannot be carried out and are void by law. Failure to comply with the law in the process of merger and acquisition can lead to serious legal consequences. In Article 29 (1) of the Anti-Monopoly Act entrepreneurs who do not report merger activities and acquisitions to KPPU are threatened with sanctions and cancellation of mergers and companies canceling their merger transactions by the KPPU is not considered as a subject of law, the absorbing company (an entity that merges itself) must carry out re-establishment under the regulations in force.